Muscle organization in individuals with and without pain and joint dysfunction - Nickel, J C; Gonzalez, Y M; McCall, W D; Ohrbach, R; Marx, D B; Liu, H; Iwasaki, L R (Journal of dental research, 2012)
Central nervous system organization of masticatory muscles determines the magnitude of joint and muscle forces. Validated computer-assisted models of neuromuscular organization during biting were used to determine organization in individuals with and without temporomandibular disorders (TMD). Ninety-one individuals (47 women, 44 men) were assigned to one of four diagnostic groups based on the presence (+) or absence (-) of pain (P) and bilateral temporomandibular joint disc displacement (DD). Electromyography and bite-forces were measured during right and left incisor and molar biting. Two three-dimensional models employing neuromuscular objectives of minimization of joint loads (MJL) or muscle effort (MME) simulated biting tasks. Evaluations of diagnostic group and gender effects on choice of best-fit model were by analysis of variance (ANOVA) and Tukey-Kramer post hoc tests, evaluations of right-left symmetry were by Chi-square and Fisher's exact statistics, and evaluations of model accuracy were by within-subject linear regressions. MME was the best-fit during left molar biting in +DD individuals and incisor biting in men (all p < 0.03). Incisor biting symmetry in muscle organization was significantly higher (p < 0.03) in healthy individuals compared with those with TMD. Within-subject regressions showed that best-fit model errors were similar among groups: 8 to 15% (0.68 ≤ R(2) ≤ 0.74). These computer-assisted models predicted muscle organization during static biting in humans with and without TMDs.